DETERMINATION CARBOHYDRATE LEVEL OF WHITE RICE IN THE RICE COOKER HEATING PROCESS WITH TIME VARIATION - Luh Made Widhyasari; Ni Luh Nova Dilisca Dwi Putri; Putu Ayu Parwati (Stikes Wira Medika Bali, 2017)
Rice is the staple food of processed rice commonly consumed by the people of Indonesia. The content of rice consists of carbohydrates, protein, fat, and water. Carbohydrates have a role as a major energy source for humans to perform its activities. People tend to prefer to consume rice in a warm environment. Rice warmers are widely used in the community is a rice cooker. The purpose of this study is to determine the carbohydrate levels in rice heated in a rice cooker with a time variation of 0; 6; 12; 18 and 24 hours. This type of research is quantitative where the data is presented without statistics and described descriptively. This study was conducted in May 2017 using a sample of rice heated in a rice cooker with variations of time. Result: Obtained carbohydrate content from time variation 0 hours, 6 hours, 12 hours, 18 hours and 24 hours that is 16,87%, 14,22%, 10,26%, 9,30% and 8,97%. Based on the results of research can be concluded that the longer time the rice in the rice cooker, the lower the carbohydrate level. This research can be used as input matter for society to arrange healthy lifestyles in concuming carbohydrate everyday especially for diabetics is expected to not consume rice immediately after ripe, but wait a few minutes to decreas carbohydrate level.